Synthesis of the full-length hepatitis B virus core protein and its capsid formation - Aoki, Keisuke; Tsuda, Shugo; Ogata, Naoko; Kataoka, Michiyo; Sasaki, Jumpei; Inuki, Shinsuke; Ohno, Hiroaki; Watashi, Koichi; Yoshiya, Taku; Oishi, Shinya (Organic & biomolecular chemistry, 2024)
Chronic infection with hepatitis B virus (HBV) is a major cause of cirrhosis and liver cancer. Capsid assembly modulators can induce error-prone assembly of HBV core proteins to prevent the formation of infectious virions, representing promising candidates for treating chronic HBV infections. To explore novel capsid assembly modulators from unexplored mirror-image libraries of natural products, we have investigated the synthetic process of the HBV core protein for preparing the mirror-image target protein. In this report, the chemical synthesis of full-length HBV core protein (Cp183) containing an arginine-rich nucleic acid-binding domain at the C-terminus is presented. Sequential ligations using four peptide segments enabled the synthesis of Cp183 via convergent and C-to-N direction approaches. After refolding under appropriate conditions, followed by the addition of nucleic acid, the synthetic Cp183 assembled into capsid-like particles. Protocols for chemical synthesis and in vitro assembly of the hepatitis B virus full-length core protein (Cp183) were investigated.